Editorial note - Petryk, H. (Archives of Mechanics, 2020)
The following articleARCHIVES OF MECHANICSArch. Mech. 71 (2), 155–171, 2019, DOI: 10.24423/aom.3057Influence of initial density of granular stack on transient regime of homogeneous fluidizationA.S. DRAME, L. WANG, B. DIOURTEhas been withdrawn.